Utilization of Secang (Caesalpinia Sappan L) Wood Extract in Optimization of Liquid Soap Formulation - Dwi Saryanti; Iwan Setiawan (Pharmacon: Jurnal Farmasi Indonesia, 2018)
One of the plants used in traditional medicine is secang (Caesalpinia sappan L.). Liquid soap is now widely produced because of its practical use and better appearance. The use of anionic surfactants can cause irritation and dry skin due to strong binding of skin proteins. Cocamid DEA is used as nonionic surfactant in the liquid soap formulation to reduce the irritation caused by the anionic surfactant. The determination of optimal formula of secang wood extract liquid soap used D-optimal method by using parameter of pH test, viscosity, density and antibacterial activity. The organoleptic, pH, viscosity, density, antibacterial activity, foam stability, and physical stability of optimal formula were tested by cycling test. The ratio of sodium lauryl sulfate:cocamid DEA in optimal formula of secang wood extract liquid soap was (98.95: 1.05). The optimal formula of liquid soap has pH 4.6, viscosity 51.67 dPas, density 1.06 g / mL, antibacterial activity of Staphylococcus aureus 16.2 mm and foam stability 96.67%.